An injectable extracellular matrix for the reconstruction of epidural fat and the prevention of epidural fibrosis. (7th June 2016) - Lin, Cheng-Yi; Liu, Tse-Ying; Chen, Mei-Hsiu; Sun, Jui-Sheng; Chen, Ming-Hong
Abstract: Extensive epidural fibrosis is a common complication following spinal surgery and can cause pain and limited mobility. In the present study, a novel biomimetic approach was developed to prevent postsurgical adhesion of the dura. We aimed to reconstruct epidural fat, which prevents scar-tissue adhesion, through the development of an injectable decellularized adipose matrix (DAM)-containing hyaluronic acid (HA) hydrogel loaded with adipose stromal cells (ASCs). Injectable DAM was prepared from porcine adipose tissue by four freeze—thaw cycles with subsequent pepsin digestion. Residual analyses confirmed the efficacy of detergent-free decellularization, while most sulfated glycosaminoglycans and collagen were preserved. The Transwell migration assay demonstrated the anti-infiltrative property of the DAM-containing HA hydrogel. After 14 d of 3D culture, the DAM-containing HA hydrogel showed inductive potential in the adipogenic differentiation of ASCs. For an in vivo study, the ASC-loaded DAM-containing HA hydrogel (DAM/ASC-incorporated HA hydrogel) was injected into adult laminectomized male rats, and the results were assessed by microscopic histological examination. The in vivo data indicated that HA hydrogel, DAM, and ASCs were all required for the ability of the engineered fat tissue to block the invasion of the fibrous tissue. Our results suggested that this injectable DAM/ASC-incorporated HA hydrogel has potential applications in minimally invasive surgery for soft-tissue reconstruction and epidural fibrosis prevention.